The Analysis of Politeness Strategy between Moana and Maui in the “Moana” Cartoon Movie - Dwi Rahma Fitri; Rini Afrilesa J; Vera Magria (Krinok:Jurnal Linguistik Budaya, 2020)
This thesis entitled The Analysis of Politeness Strategy between Moana and Maui in the Moana Cartoon Movie. The aims of this research are  to find out and explain the types of politeness strategies used by Moana and Maui in Moana  cartoon movie. The researcher  used descriptive-qualitative method. The data are in form of  the utterances between Moana and Maui.In collecting the data the researcher use non participant technique and the researcher did download technique, watching and note taking to collect the data. In technique of analyzing the data the researcher uses referential method to explain the data in which the tool device refers to the referent of the language. The data are presented through formal and informal method.The result of the research, there are 4 strategies that are used by these 2 characters; bald-on record, positive politeness, negative politeness, and off record.Keywords :Politeness Strategy,  FTA, Moana and Maui.